Analysis of Risk Factors and Causes of High Maternal and Infant Mortality Rates in Rural Areas - Abraham, Muhammad Arif (Generasi Sains Indonesia, 2024)
This study aims to analyze the risk factors and causes contributing to the high maternal and infant mortality rates in rural areas. The literature review reveals that factors such as limited access to healthcare facilities, inadequate prenatal and postnatal care, lack of skilled birth attendants, and prevalent socio-cultural practices significantly impact these mortality rates. Additionally, poor maternal nutrition, insufficient antenatal education, and delays in seeking medical help during pregnancy and childbirth are identified as key contributors. In conclusion, addressing these multifaceted challenges requires a comprehensive approach that involves improving healthcare infrastructure, increasing awareness about maternal and child health, and enhancing the quality of prenatal and postnatal care services in rural areas.